2009
DOI: 10.1175/2008jas2585.1
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Order Model Investigation of the Analysis of Gravity Waves in the Ensemble Kalman Filter

Abstract: The behavior of the ensemble Kalman filter (EnKF) is examined in the context of a model that exhibits a nonlinear chaotic (slow) vortical mode coupled to a linear (fast) gravity wave of a given amplitude and frequency. It is shown that accurate recovery of both modes is enhanced when covariances between fast and slow normal-mode variables (which reflect the slaving relations inherent in balanced dynamics) are modeled correctly. More ensemble members are needed to recover the fast, linear gravity wave than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Unless there is sufficient information in the background error covariance to distribute increments in a balanced way, the unbalanced modes will enter the system, and it may be difficult to remove these modes with limited observations (Neef et al, 2006(Neef et al, , 2009. To quantify the imbalance in the SWM-EnKF, we use a nonlinear normal mode initialization (NMI) procedure (Machenhauer, 1977), which has been used in NWP to reduce the impact of inertia gravity waves caused by imbalance in the analysis increments (e.g., Kleist et al, 2009).…”
Section: Normal Mode Initializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless there is sufficient information in the background error covariance to distribute increments in a balanced way, the unbalanced modes will enter the system, and it may be difficult to remove these modes with limited observations (Neef et al, 2006(Neef et al, , 2009. To quantify the imbalance in the SWM-EnKF, we use a nonlinear normal mode initialization (NMI) procedure (Machenhauer, 1977), which has been used in NWP to reduce the impact of inertia gravity waves caused by imbalance in the analysis increments (e.g., Kleist et al, 2009).…”
Section: Normal Mode Initializationmentioning
confidence: 99%
“…A wide range of studies has been performed to examine balance in the context of 4-D data assimilation. For example, Neef et al (2006Neef et al ( , 2009) investigated balance with a loworder Lorenz-type model with the EKF and EnKF. Imbalance within SWM-DAS systems was analyzed in both 4D-Var (Courtier and Talagrand, 1990;Polavarapu et al, 2000) and EnKF (Kepert, 2009(Kepert, , 2011 using digital filter and nonlinear normal mode initialization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Szunyogh et al (2005) is an example of a case in which an EnKF-type assimilation method was able to capture a fast-varying gravity wave mode that was present in observations and not in the model forecast, indicating that flow-dependent covariance models can potentially capture unbalanced motion. Neef et al (2006) reported similar results where the EnKF was able to provide better estimates of the fast-varying modes than the linearized (extended) Kalman filter. Other techniques such as scaledependent modeling and assimilation using the ensemble Kalman filter have been attempted (Zou and Ghanem 2005) in engineering applications.…”
Section: Introductionmentioning
confidence: 61%
“…In meteorological and climatological applications, ''balance'' generally refers to the dominance of slow vortical motion over fast inertiagravity waves. In multiscale systems like the ocean or atmosphere in which modeled flows in certain regimes are expected to be balanced, it has been found that current 4D data assimilation techniques, as the EnKF and 4DVAR, could cause the excitation of spurious unbalanced motion (Polavarapu et al 2000;Houtekamer and Mitchell 2005;Neef et al 2006). This has been known to happen because of the development of unphysical correlations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation